Description of Timogenes pipanaco sp. nov., (Scorpiones, Bothriuridae) a new salt flat species from north western Argentina - Barrios-Montivero, Alexis E.; Salas, Liliana B.; Ojanguren-Affilastro, Andrés A. (Zootaxa, 2024)
We describe Timogenes pipanaco sp. nov. (Scorpiones, Bothriuridae) from north western Argentina. This species is most similar to Timogenes haplochirus Maury & Roig Alsina 1977, both sharing a shallow internal excavation in pedipalp chela of males. This is the smallest known species of the genus with males averaging 33.3 mm, and is the only species of the genus with extremely reduced stridulatory organ. This species is apparently endemic to the Pipanaco salt flat in arid north western Argentina, and is active in spring. This is the first species of genus Timogenes described after 45 years.